Understanding Strong Human Character in the Qur'an: An Analysis of M. Quraish Shihab's Interpretation in Tafsir al-Mishbah - Qotrunnada Nafisah Al Mardhiyyah; Akhmad Sulthoni; Akhmadiyah Saputra (CV. Doki Course and Training, 2025)
Strong character is the moral and spiritual foundation needed for humans to face the challenges of life. The Qur'an as a guide to life contains many verses that describe the ideal human character. One of the contemporary commentaries that examines human strong character in the Qur'an is Tafsir al-Mishbah by M. Quraish Shihab. This study aims to analyze how Quraish Shihab interprets the concept of strong character in the Qur'an and its relevance to modern life. The method used is a literature study with a descriptive-analytical approach to the verses related to human strong character. The results showed that according to Quraish Shihab, strong character in the Qur'an includes piety, patience, honesty, and courage in upholding the truth. Quraish Shihab's interpretation provides an understanding that the strength of human character is not only physical, but also includes spiritual and moral aspects that shape a person's personality. Of course, this can foster the spirit in the soul of each individual to worship Allah. This finding reinforces the importance of strong human character as the main capital in building a better individual and society. This study is expected to provide deeper insights into the concept of strong human character in the Qur'an and contribute to the insight of contemporary tafsir by applying Islamic values comprehensively.